2017
DOI: 10.1002/anie.201702292
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylations with CO2 as the CO Source and Reactivity Modifier

Abstract: A CO surrogate: In two recent studies, CO has not only been applied as a CO source in the hydroformylation of alkenes and the carbonylative Hiyama-Denmark coupling of aryl iodides, but more interestingly it also attenuates or improves the reactivity of the reactants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As one of the most inexpensive, renewable and abundant C1 resource, the utilization of carbon dioxide (CO 2 ) for syntheses of feedstock and value‐added chemicals has attracted intensive attentions from both laboratory and industry . Therefore, in recent years, great efforts have been devoted to explore and develop efficient catalysts for this purpose.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As one of the most inexpensive, renewable and abundant C1 resource, the utilization of carbon dioxide (CO 2 ) for syntheses of feedstock and value‐added chemicals has attracted intensive attentions from both laboratory and industry . Therefore, in recent years, great efforts have been devoted to explore and develop efficient catalysts for this purpose.…”
Section: Methodsmentioning
confidence: 99%
“…formamidesi ng ood to excellenty ields (75-94 %, 4a-c, 5,a nd 6). Similar as cyclic cases, acyclic symmetric and asymmetric secondarya mines were also compatible and readily converted into the desired products in moderate to excellent yields (53-93 %,[7][8][9][10][11][12][13][14]. In the case of volatile dimethylamine (for safety reason, [Me 2 NH 2 ] + ·[Me 2 NCOO] À was applied instead),am oderate yield was still presented to produce DMF (53 %, 8).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…To solve this problem, many research groups have worked on the development of CO surrogates that generate CO in situ, and several safe and facile carbonylation reactions using CO surrogates have been reported. [11][12][13][14][15][16][17][18] Recently, we and Tsuji et al independently reported Pd-catalyzed carbonylation reactions using a liquid CO surrogate, phenyl formate. It was found to react with weak bases (e.g., NEt 3 ) at elevated temperatures to form CO and phenol, and could be employed in external-CO-free carbonylation reactions in situ.…”
mentioning
confidence: 99%